Effect of Sintering Temperature on Flexural Strength of Two Types of Zirconia - Armaghan Shahbazi; Fariborz Vafaei; Amirarsalan Hooshyarfard; Erfan Nosrati; Masood Nazari; Maryam Farhadian (Tehran University of Medical Sciences, 2022)
Objectives: Any change in the sintering process can directly affect the micro-structure and properties of zirconia. This study sought to assess the effect of sintering temperature on flexural strength of IPS e.max ZirCAD MO Ivoclar (EZI) and CopraSmile White Peaks Symphony (WPS) zirconia blocks. Materials and Methods: In this in vitro, experimental study, 30 EZI and 30 WPS zirconia blocks measuring 10 x 10 x 1 mm were milled and sintered at 1440, 1500 and 1530°C in three subgroups. The flexural strength of the specimens was measured by a testing machine with piston-on-3-ball method according to ISO2015. Data were analyzed using one-way ANOVA. Results: The mean flexural strength was 1.31±0.49, 1.09±0.24 and 1.29±0.48 MPa in 1440, 1500, and 1530°C subgroups of EZI, and 1.44±0.61, 1.18±0.35, and 1.33±0.54 MPa in 1440, 1500, and 1530°C subgroups of WPS zirconia, respectively. Two-way ANOVA revealed that the effects of zirconia type (P=0.484), temperature (P=0.258) and their interaction (P=0.957) on flexural strength were not significant. Conclusion: Increasing the sintering temperature from 1440°C to 1530°C did not increase the flexural strength of EZI or WPS zirconia.